2017
DOI: 10.18632/oncotarget.22330
|View full text |Cite
|
Sign up to set email alerts
|

The association of MPO gene promoter polymorphisms with Alzheimer’s disease risk in Chinese Han population

Abstract: AimThe objective of this study was to explore the genetic association of myeloperoxidase (MPO) gene polymorphisms with risk of Alzheimer's disease (AD).MethodsBlood samples were collected from 116 AD patients and 134 age and gender matched healthy individuals. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was utilized to confirm MPO polymorphisms in promoter region. Plasma concentration of MPO was detected by enzyme-linked immuno sorbent assay. Genotype distributions of MPO poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Furthermore, an interaction was identified between MPO and the APOE ε4 allele, the most common genetic risk factor for late onset AD 41 . Following studies, however, exhibited contradicting findings regarding the association of the 463G/A polymorphism with AD (Crawford et al, 2001; Combarros et al, 2002; Leininger-Muller et al, 2003; Ji and Zhang, 2017). Green et al (2004) have reported elevated MPO immunoreactivity and activity in the cortices of AD patients, along with increased prevalence of its oxidation products.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, an interaction was identified between MPO and the APOE ε4 allele, the most common genetic risk factor for late onset AD 41 . Following studies, however, exhibited contradicting findings regarding the association of the 463G/A polymorphism with AD (Crawford et al, 2001; Combarros et al, 2002; Leininger-Muller et al, 2003; Ji and Zhang, 2017). Green et al (2004) have reported elevated MPO immunoreactivity and activity in the cortices of AD patients, along with increased prevalence of its oxidation products.…”
Section: Discussionmentioning
confidence: 97%
“…The lysosomal enzyme and peroxidase activity were analyzed in the MPO (23) , which plays a role in the regulation of inflammatory responses, lysosomal pathway, tissue damage, lipid metabolism, and oxidative damage (24) . Not only is MPO activity engaged in the host defense physiology against microorganisms, but also it is involved in the pathophysiology of atherosclerosis, respiratory tract and CNS diseases, and cardiac dysfunction (25) .…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the genotypes of A/A and MPO -463G/A have a diminished risk of colorectal adenomas, acute leukemia, gastric, lung, and ovarian carcinoma (32) . Ji et al found MPO rs2333227 variant was positively associated with the risk of Alzheimer's disease among the population in China (24) . Galecki et al declared a statistically significant difference in genotype distribution and allele frequency of MPO rs2333227 variants between depressive patients and healthy controls (34) .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 169 studies were excluded due to duplication, 306 studies were deleted through fulltext review or title and abstract screening, and 12 studies were excluded for other deficiencies. Then, nine publications (10 independent case-control studies) involving 1630 patients and 1630 controls were included to assess the association between MPO rs2333227 G>A polymorphism with AD risk [18,[23][24][25][26][27][28][29][30]. Eight studies were conducted in Caucasian or European populations, and two studies were conducted in Asian populations.…”
Section: Study Characteristicsmentioning
confidence: 99%